(untitled) (Fiep Bulletin - online, 2017)
Vitamin D deficiency is a common finding in our adult population, due to a combination of factors such as decreasedintake and absorption, limited exposure to sun light, time of year, latitude, skin pigmentation, medications, age, and the use ofsunscreens. The aim of this study was to investigate the benefits that vitamin D provides to the health of the population, throughthe analysis of current publications, such as: scientific articles, books, national and international thesis. Among the benefits thatcurrent studies point out, are the use of vitamin D as an adjunct to the health and well-being of the population, as well as: skin healing, bone health, systemic arterial hypertension, type I diabetes, cancer, multiple sclerosis, psoriasis, rheumatoid arthritis,epilepsy in the elderly, vitiligo and also the immune modulatory effect guaranteeing the strengthening of the immune system.